PENGARUH SUKU BUNGA SBI, IMPOR DAN EKSPOR TERHADAP KURS RUPIAH/DOLAR AMERIKA SERIKAT TAHUN 2010-2018 - Jaya, Nyoman Herry Apryanta; Setiawina, Nyoman Djinar (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 11 No 8 (2022): VOL11NO 8, AGUSTUS 2022 [2900-3323], 2022)
Exchange rate the value of country's currency with value of another country's currency, which used to conduct international trade. Currency exchange rates or exchange rates are one of the most important macroeconomic variables, because movements in the exchange rates will affect economic stability. The research objectives to 1) analyze the effect of SBI interest rates, imports, and exports simultaneously on the rupiah / US dollar exchange rate in 2010-2018. 2)  partially analyze the effect of SBI, Import, and Export interest rates on the rupiah / US dollar exchange rate in 2010-2018. 3) determine the variables that have a dominant effect on the SBI, Import, and Export interest rates on the rupiah / US dollar exchange rate in 2010-2018. This study uses secondary data and multiple linear regression analysis. The results are 1) SBI interest rates, imports, and exports simultaneously have significant effect on the exchange rate / exchange rate. 2) SBI, Import, and Export interest rates have positive significant effect on the exchange rate / exchange rate. 3) The variable that has a dominant influence is the export variable. Keywords: Rupiah / United States dollar exchange rate, SBI interest rate, Import and Export